Is occupational arsenic exposure a possible causative agent of breast cancer for a young female laboratory technician? a case-study - Heng, Pei Pei; Hanizah Mohd Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2023)
A 28-year-old female laboratory technologist who was exposed to highly concentrated inorganic arsenic for 7 years, 25 hours a week, presented with left breast cancer. When most epidemiologic evidence reported by the International Agency for Research on Cancer (IARC) supported the relationship between arsenic exposure and cancers of lung, skin and bladder; literature had documented increased risk of breast cancer in specific populational subgroups due to the estrogen-like activity of arsenic. The existing available control measures are restricted to the administrative control such as training and job rotation, hence making the causal assessment of occupational cancer is challenging due to the lack of relevant data on the worker’s biological monitoring and environmental exposure monitoring data,together with the insufficient genetic composition information like Breast Cancer Genes1 (BRCA1). Moreover, the poor work practice and hygiene had made the exposure through dermal contact and digestion possible. The interpretation of work causal relationship while distinct occupational cancer from those of non-occupational must consider individual susceptibility as low-level short-period exposure might increase the risk for certain worker. Therefore, a systematically collected medical surveillance data along with industry hygiene data is highly recommended in order to assist in the refinement of human dose-response relationship of specific work carcinogen.